Kembali Beraktivitas Seksual Pasca Bedah Pintas Arteri Koroner - Dwita R Desandri R Desandri; AH Raynaldo; Basuni Radi; Siti F Supari F Supari; Budhi Setianto; Dede Kusmana (Jurnal Kardiologi Indonesia, 2016)
Surgical coronary revascularization can affect the quality of life and psychosocial functions, including the return of sexual activity. A 43-year-old male patient underwent four graft coronary artery bypass (CABG) surgery at National Cardiovascular Center Harapan Kita. The second phase of rehabilitation results showed patient’s functional capacity is 9.75 METs and ischemic negative response. Before surgery, patient often experienced chest pain during intercourse. The patient must consume sublingual isosorbide dinitrate (ISDN). Currently the patient is no longer feel chest pain during intercourse, but he was still afraid to do intercourse and reduce the activity frequency.Return to sexual activity after undergoing CABG surgery is a common concern. Cardiac rehabilitation program and sexual counseling can help patients to return to their sexual function and activity.